2010
DOI: 10.1016/j.neurobiolaging.2008.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated changes in synaptic lipid raft proteins revealed by two-dimensional fluorescence difference gel electrophoresis

Abstract: Brain aging is associated with a progressive decline in cognitive function though the molecular mechanisms remain unknown. Functional changes in brain neurons could be due to age-related alterations in levels of specific proteins critical for information processing. Specialized membrane microdomains known as 'lipid rafts' contain protein complexes involved in many signal transduction processes. This study was undertaken to determine if two-dimensional fluorescence difference gel electrophoresis (2D DIGE) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…Another interesting finding was the decrease in dynamin-1, a guanosine triphosphatase (Yang et al, 2008) that was also observed by VanGuilder et al (2010) in Fischer 344 × Brown Norway (F1) hybrid male rats (Chadwick et al, 2012;Freeman et al, 2009;Jiang et al, 2010) and Ottis et al (2013) in male outbred Wistar rats (Ottis et al, 2013). In the brain, dynamin-1 plays a pivotal role in the fission stage of synaptic vesicle endocytosis and thus neurotransmission (Ferguson et al, 2007) as well as in the mechanical stabilisation of F-actin bundles in growth cone fillipodia and thus growth cone motility and the elongation and guidance of axons to synaptic targets (Yamada et al, 2013).…”
Section: Brainmentioning
confidence: 73%
See 1 more Smart Citation
“…Another interesting finding was the decrease in dynamin-1, a guanosine triphosphatase (Yang et al, 2008) that was also observed by VanGuilder et al (2010) in Fischer 344 × Brown Norway (F1) hybrid male rats (Chadwick et al, 2012;Freeman et al, 2009;Jiang et al, 2010) and Ottis et al (2013) in male outbred Wistar rats (Ottis et al, 2013). In the brain, dynamin-1 plays a pivotal role in the fission stage of synaptic vesicle endocytosis and thus neurotransmission (Ferguson et al, 2007) as well as in the mechanical stabilisation of F-actin bundles in growth cone fillipodia and thus growth cone motility and the elongation and guidance of axons to synaptic targets (Yamada et al, 2013).…”
Section: Brainmentioning
confidence: 73%
“…A closer investigation of age-related differential expression of proteins in lipid rafts of neuronal synaptic plasma membrane preparations from Fisher 344/Brown Norway hybrid (F344/BNF1) rats (5 and 34 months of age) was carried out using 2-D DIGE MALDI-TOF/TOF and ultra Hybrid Mass Spectrometer (LTQ-FT) (Jiang et al, 2010). It revealed a total of 40 identified and significantly diminished proteins in these specific cholesterol-and sphingolipid-rich domains of neurons in older rats.…”
Section: Brainmentioning
confidence: 99%
“…The aging brain demonstrates region-specific alterations in neuronal morphology, reduced structural plasticity (30, 31) and dendritic branching (54), and a decreased capacity to regenerate (27, 55). With age the brain undergoes changes in plasma membrane biophysical properties (i.e., decreased cholesterol, gangliosides, and phosphoinositides) (56), impaired cholesterol synthesis and lipoprotein transport (55), changes in the molecular composition of the postsynaptic membrane (54) accompanied with reduced MLR-associated synaptic proteins (57), and diminished pre-synaptic vesicle exocytosis and subsequent neurotransmitter release; the latter are due to cholesterol depletion or cholesterol redistribution from cyto to exofacial leaflet of the plasma membrane ultimately leading to altered recruitment of SNARE complexes (56). Akin to these findings, previous work from our group demonstrated that Cav-1 and synaptic components (e.g., PSD-95, NMDAR, AMPAR, TrkB) are decreased in the aged brain, specifically in synaptosomes and MLRs isolated from the hippocampus (33, 54).…”
Section: Discussionmentioning
confidence: 99%
“…; Jiang et al . ). The synaptosomes recovered from the gradient were lysed in a hypotonic buffer (3 mM Tris‐HCl, pH 8.5) containing a cocktail of protease inhibitors and centrifuged at 64 200 g for 15 min.…”
Section: Methodsmentioning
confidence: 97%